Critical thinking skills for education students - Eales-Reynolds, Lesley-Jane; Judge, Brenda; Jones, Patrick; McCreery, Elaine (Study skills in education, 2013)
This title will help education students develop their understanding of critical analysis. It outlines the skills needed to examine and challenge data and encourages an appreciation of how this way of thinking can enrich the personal and professional development of students.